2023
DOI: 10.1021/acsanm.3c04558
|View full text |Cite
|
Sign up to set email alerts
|

N/P Codoped Carbon Nanofibers Coupled with Chrysanthemum-Like Cobalt Phosphide Hybrid for Stable Lithium–Sulfur Batteries

Xiaoning Zhang,
Chao Ma,
Yiqiong Wang
et al.

Abstract: Lithium–sulfur batteries demonstrate enormous energy density and are promising forms of energy storage. Unfortunately, the slow redox kinetics and polysulfide shuttle effect are some of the factors that prevent its development. To address these issues, the combination of nitrogen/phosphorus codoped carbon nanofiber membrane with chrysanthemum-like cobalt phosphide hybrid (CoP@NP-CF) and utilized Li2S6 catholyte for lithium–sulfur battery. The conductive NP-CF facilitates fast electronic/ionic transport and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 67 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…The full XPS spectrum displays S 2s and S 2p peaks in Figure a, showing the presence of sulfur species in the cycled sample. Figure b shows the high-resolution N 1s XPS spectrum, and it can be found that the peak intensity of the pyrrolic-N group decreases significantly due to the adsorption of polysulfides. , In the high-resolution S 2p XPS spectrum (Figure c), there are typically several peaks at 169.1, 167.5, 164.5, and 162.3 eV, corresponding to polysulfide oxidation, Li 2 SO 3 produced by the electrolyte, sulfur, and lithium sulfide (Li 2 S), respectively. Figure d,e shows the high-resolution XPS spectra of Co 2p and Fe 2p, and the characteristic peaks correspond to the CoFe alloy, respectively. However, the binding energies of multivalence states of Co and Fe shift to a lower binding energy after cycling, which is attributed to the chemisorption of polysulfide species by the CoFe nanoalloy particles. …”
Section: Results and Discussionmentioning
confidence: 95%
“…The full XPS spectrum displays S 2s and S 2p peaks in Figure a, showing the presence of sulfur species in the cycled sample. Figure b shows the high-resolution N 1s XPS spectrum, and it can be found that the peak intensity of the pyrrolic-N group decreases significantly due to the adsorption of polysulfides. , In the high-resolution S 2p XPS spectrum (Figure c), there are typically several peaks at 169.1, 167.5, 164.5, and 162.3 eV, corresponding to polysulfide oxidation, Li 2 SO 3 produced by the electrolyte, sulfur, and lithium sulfide (Li 2 S), respectively. Figure d,e shows the high-resolution XPS spectra of Co 2p and Fe 2p, and the characteristic peaks correspond to the CoFe alloy, respectively. However, the binding energies of multivalence states of Co and Fe shift to a lower binding energy after cycling, which is attributed to the chemisorption of polysulfide species by the CoFe nanoalloy particles. …”
Section: Results and Discussionmentioning
confidence: 95%
“…Energy storage systems with large energy density are critically needed to satisfy the rapidly growing energy demands of electric vehicles and portable electronics . Lithium–sulfur batteries (LSBs) are considered some of the highly promising core technologies in post-lithium-ion batteries due to the ultrahigh theoretical specific capacity of sulfur (1675 mAh g –1 ) and excellent energy density (2600 Wh kg –1 ), which can overcome the limitations of the insertion-oxide cathode and graphite anode in lithium-ion batteries. , Currently, the key issue in developing an LSB electrode material is how to effectively enhance its energy density and cycle stability. , In response to the above issues, many research efforts have been focused on exploring materials and the design of composite structures and morphologies, with strategies such as modulation of morphologies, , introduction of catalysts, heterostructure design, , defect modification, , and interface engineering. , Despite substantial progress, their further development still encounters some bottlenecks due to the intractable large volume change of sulfur particles, low utilization of sulfur, and sluggish reaction kinetics . Accordingly, instead of developing active materials, fully exploiting the advantages of certain materials may be more advantageous .…”
Section: Introductionmentioning
confidence: 99%